Delayed recognition of mpox on an inpatient psychiatric unit: a case report and investigation - Waleed Malik; Simon Dosovitz; Jonathan Whitehouse; Nafisa Reza; Sharmin Khan; Justin Chan (Antimicrobial Stewardship & Healthcare Epidemiology)
This report describes a delayed recognition of mpox in a patient admitted to an inpatient psychiatry unit, resulting in potential exposures to staff and patients. We detail the investigation and risk mitigation efforts and emphasize the importance of prompt identification and isolation in congregate healthcare settings to prevent transmission.